Diseño de un sistema para control de la manipulación en gabinetes de medidores de energía eléctrica mediante alarmas y bloqueos (2022)
Initially, with the introduction and background, we know how public service companies, especially electricity companies, have avoided sanctions and embezzlement due to the loss control plan implemented, as well as how CREG has created plans and strategies to regulate the amount of energy losses. It was justified with the approach of real solutions that aim to avoid losses due to non-registration of energy due to fraud, accidents due to improper manipulation or failures of the energy service and apart from obtaining the title as Technologist in Industrial Electromechanical Maintenance. The objectives focused on the design of the system that manages to block and alert when an electrical energy meter cabinet is violated or manipulated without prior authorization. For this reason, it began by carrying out a survey to find out the shortcomings in cabinets of electrical energy meters that allow their easy handling and due to this, failures in the service. In this survey, four specific questions were basically asked about the perception and visualization of violation in cabinets that house the energy meter of the selected users, as well as two basic data that are the meter number and address that complement the information differentiating the surveyed users. Subsequently, the circuit was designed in a software meeting the expectations raised in the project and with this the expected results were obtained. This design included the calculation of busbars, connections, and protections to be used for the implementation of the system to obtain the proposed objectives. Due to the above, the project is satisfactorily concluded, obtaining learning results that contribute to the experience related to the program studied and enriches the technical concepts transferred during the academic program.